Evidências de desequilíbrio fluvial na bacia hidrográfica Rio das Antas (SC) - Pagno, Fabiana (2021)
Morphometric studies are important to obtain data and information in relation to a hydrographic basin, such as: information on the environmental dynamics of the studied area; assistance in the management of water resources; provides data to assess areas susceptible to flooding; presents data on land use and occupation, structural and lithological influence, among others. Considering these factors, the objective of this work was to verify the existence of fluvial imbalances in the Rio das Antas Hydrographic Basin, located in the Far West of the State of Santa Catarina. This study was carried out in a GIS (Geographic Information System) environment, organized on a cartographic basis at a scale of 1:50,000, with data extracted from geographic maps of the Ministry of Defense - Brazilian Army Department of Science and Technology Geographical Service Directorate, the Brazilian Institute of Geography database, as well as a geographic database of state institutions in Santa Catarina (EPAGRI). The areal morphometric parameters of the Rio das Antas hydrographic basin and 24 of its representative tributaries were analyzed, where it was verified: With the ordering of drainage channels and hierarchization, it was possible to verify that the Rio das Antas is a 6th order channel. The total area (268,077 km²), total extension (205,699 km) were checked. With the analysis of drainage patterns, angular, subdendritic, parallel, dendritic, rectangular, subparallel and truss patterns were detected; and drainage properties that refer structural influence and possible tipping of the hydrographic basin to the right bank, as verified with the application of the Basin Asymmetry Factor (FAB); The longitudinal profile of the Rio das Antas presents along its course areas in balance and imbalance (areas in rise and subsidence), and several topographical projections of great amplitude; With the spatialization of the anomalies it was possible to verify that most of the anomalies are concentrated in Fáceis Paranapanema, so it is believed that it presents greater resistance in relation to the other facies, which allows the formation of topographical bumps; The 1st order anomalies present in the BH Antas are related to structural control, marked by the presence of faults and fractures and in lithological changes, while the 2nd order anomalies present in the BH Antas are distributed throughout the basin and their occurrence is due to the fact structural control (faults and fractures), but also in the area where channels meet, as there is a significant increase in flow and changes in sediment load textures. It appears that the hydrographic basin of Rio das Antas has fluvial imbalances along its basin and a strong structural and lithological control. From the application of the RDE Excerpt/Total Index, anomalous zones in the drainage network were detected, referring to Neotectonic interference in the studied area.